Cross-Border Transmission: Analyzing Oil Shocks Pass-Through in U.S. and Canada - Aiyash, Eiman; Abou-Zaid, Ahmed (International Journal of Economics and Financial Issues, 2026)
This paper investigates the degree of oil prices pass-through to import, producer, and consumer prices in Canada and the United States from 1980 to 2017 using a Structural Vector Auto-Regression (SVAR) model. The results indicate a positive long-run correlation between oil prices and aggregate price levels. The impulse response function reveals a persistent and incomplete pass-through for oil prices, i.e., 0.04 for Canada and 0.25 for the U.S. Greater pass-through exists in an economy with more oil import share. Consistent with the impulse response function, variance decomposition reveals that oil price shocks in the United States are the primary cause of the variation in import and producer prices. However, in Canada, oil price shocks explain the variation in producer and consumer prices.